Household Food Insecurity in DKI Jakarta Province at The Beginning of The Covid-19 Pandemic - Lutfi Hamdani Sutikno; Budiasih Budiasih (Politeknik Statistika STIS, 2021)
Food insecurity is a global issue that’s concern not only in poor and developing countries, but also in developed countries. Its conditions have worsened since the beginning of the Covid-19 pandemic where social restrictions and economic contraction caused many people to lose their jobs, incomes, and increased poverty. DKI Jakarta was one of the most economically affected provinces at the beginning of the Covid-19 pandemic where economic growth in the first quarter of 2020 recorded grow 5.06 percent year on year (the lowest in the last ten years) and slowed down by 0.56 percent overall quarter to quarter, and an increase of poverty 1.11 percent, the highest in Indonesia. This study examines the effect of household characteristics in DKI Jakarta on their food insecurity status at the beginning of the Covid-19 pandemic. The data used is the March 2020 Susenas which was analyzed descriptively and inferentially using firth logistic regression. The results showed that there were 4.47 percent of households in DKI Jakarta had food insecurity status at the beginning of the Covid-19 pandemic. In general, households with food insecurity status are poor, don’t have social security, the head of the household doesn’t work and less than high school education.